Effectiveness of community-based mangrove management for coastal protection: A case study from Central Java, Indonesia. (1st May 2023) - Damastuti, Ekaningrum; van Wesenbeeck, Bregje K.; Leemans, Rik; de Groot, Rudolf S.; Silvius, Marcel J.
Abstract: Management and restoration of mangrove forests to protect coasts are promoted in many countries, including Indonesia. Indonesian mangrove forests are actively restored and managed by local communities for their ecosystem services, including coastal protection. Whether community-based mangrove management (CBMM) is effective is still debated. Our study analysed the effectiveness of different CBMM practices in four Central Javan communities by analysing the capacity of their mangrove forests to protect against coastal hazards. We used complementary interviews, field assessments and literature reviews to collect the necessary information. The overall CBMM performance and success significantly differed for each community's mangrove rehabilitation effort and the resulting coastal protection service. Of the four communities, Bedono performed best in terms of mangrove coverage, forest structure and restored coastal protection service. This is explained by multiple factors, such as application of long-term and integrated CBMM approaches, involving appropriate maintenance and additional measures to reduce wave energy. Our results can help governments, practitioners and communities to better understand the factors that contribute to CBMM's success and failure when restoring and managing mangrove forests and protecting coasts. Highlights: Community-Based Mangrove Management can achieve enhanced coastal protection. Long-term and integrated approaches are needed for enhancing coastal protection. Additional protective measures are necessary for eroding coastal areas. Strategic collaboration between institutions is critical for sustainable results.